An ultrasensitive chemiluminescent method for the tanshinol borneol ester determination and its pharmacokinetic analysis. (17th May 2013) - Nie, Fei; Bu, Min; Wu, Lihong; Zheng, Jianbin
ABSTRACT: Tanshinol borneol ester (DBZ), a chemical combination of danshensu and borneol, is an experimental drug that exhibits efficacious anti‐ischemic activity in animal models. In this work, an ultrasensitive chemiluminescence (CL) method for the determination of DBZ was established based on the inhibitory effect of DBZ on the CL signal produced from the reaction between potassium permanganate and luminol in alkaline solution. The CL intensity responded linearly to the concentration of DBZ in the range 2.0 × 10 ‐10 to 4.0 × 10 ‐8 g/mL with a detection limit of 7 × 10 −11 g/mL. The relative standard deviation (RSD) was 3.8% for 4.0 × 10 −9 g DBZ ( n  = 11). The proposed method showed characteristics of high sensitivity, simple device and quick. In addition, this proposed method had been applied satisfactorily to the analysis of DBZ in blood. The pharmacokinetics of DBZ in rat has also been studied using the CL method. Copyright © 2013 John Wiley & Sons, Ltd.